Problematika Substantif Perppu Nomor 1 Tahun 2013 Tentang Mahkamah Konstitusi - Ni’matul Huda (Jurnal Konstitusi, 2016)
Constitutionally, the issuance of Government Regulation in Lieu of Law is the subjective right of the President based on the state of exigencies, but its formation should alway fulfill good, proportional and prudent principles of lawmaking. Eventhough the objective of  issuing  the  Government  Regulation  in  Lieu  of  Law on Constitutional Court is to restore public trust and credibility of Constitutional Court Justices, the content of the regulation may not be contradictional with the 1945 Constitution of the Republic of Indonesia. In order that there is no distortion  in the use of subjective right of the President in issuing the regulation, the House of Representatives must objectively scrutinize whether the regulation is reasonable to be promulgated as a law ar must be denied.